(untitled) (Research, Society and Development, 2022)
The present research analyses the double paternity decision judged by the Federal Supreme Court, whose procedural object consists of biological / social paternity and pluriparentality. In the present case, the author (F. G.) is the biological daughter of A.N. (father), and at birth, was registered as daughter of I. G., with a claim of biological paternity recognition, independent of socio-affective paternity, despite the preponderance of socio-affective paternity in detriment of the biological one. What is the hermeneutic view of the Federal Supreme Court (STF) in the decision on double paternity? The hermeneutics of the Brazilian Supreme Court becomes sufficient to demonstrate that it has an established position within the scope of the Constitutional State paradigm, in the supremacy and valorization aspect of the Constitution normative force, adopting a re-reading of the Civil Code in the light of the Constitution. In parallel to biological filiation, the protection of the parenthood bond, built only from affection, demonstrates the interpretation of the legal protection (tutelage) possibility independent of the parenthood modality, based on the principle of the human person dignity, the pursuit of happiness and the responsible parenthood. The following thesis is signed: "The socio-affective paternity, declared or not in public registry, does not prevent the bond recognition of concomitant affiliation based on biological origin, with all its patrimonial and off-balance consequences ". It concludes that the posed decision admitted the viability of double paternity: the possibility of a person (son / daughter) having two parents with the respective rights and duties in this legal relationship of affiliation, as in the exercise of the family power. In this way, new judicial questions may arise, for example, in case of inheritance if the possessions will be received from both parents, if social security benefits may be received from both parents, or even in the increase of the number of parents (triple paternity) in cases of vitro fertilization.